Valoração ambiental do Parque Estadual do Cocó – Ceará - Queirós, Ana Rhennara Silva (2020)
The valuation of environmental goods and services, based on the use of different valuation methods, is an important tool that can assist in decision making for the definition of public and private policies on the management of goods and services from natural resources. In urban centers, the creation and maintenance of spaces for environmental preservation has been one of the difficulties faced by public managers. In this sense, there was a need to monetarily value the Cocó State Park, located in the city of Fortaleza - CE, which covers an area of ​​1,571 hectares and which recently became a State Conservation Unit for Integral Protection. The Park provides various services to society, such as trails, boat trips and numerous other activities that provide contact with nature. The Travel Cost Method (MCV) and the Contingent Valuation Method (MVC) were applied - based on the willingness to pay (DAP) of its visitors for a protection fee to the Park. Based on the DAP, the profile of the interviewees was analyzed from a logistic regression to determine which of the variables had significance in the decision to be, or not, willing to pay. It was observed that the variables age, expenses, number of dependents, education and income are significant for PAD; the first two have an indirect relationship, and the last three have a direct relationship with DAP. In total, 68.3% of people were willing to pay a preservation fee, this fee was estimated at R $ 3.12 per visit, generating an annual amount of R $ 666,624.2, according to MVC. In terms of MCV, this amount corresponds to R $ 5.67 / person / visit, generating an amount of R $ 1,206,547.65 per year. Obtaining a reference value for the Parque Estadual do Cocó may provide subsidies to the government in order to guide its management process.